Abstract ID: 120 Performance evaluation of the Siemens Biograph6 PET/CT imaging system using GATE Monte Carlo simulation. (October 2017) - Jozi, Hanieh Sadat; Fakhroo, Saba; Saeedzadeh, Elham; Geramifar, Parham
Abstract : Introduction: As the performance of a PET scanner depends not only on the scintillating material but also on the scanner design.[1], researchers use the Monte Carlo simulation in designing the scanners or evaluating their performance and optimizing the functional parameters before commercialization. In this study, was simulated a clinical PET/CT scanner with LSO crystal using Monte Carlo method for the purpose of investigation of the performance and obtaining the optimal patient injected activity. Materials and methods: The PET scanner of the Siemens Biograph6 PET/CT system was simulated using GATE Monte Carlo simulation code[2] . Sensitivity, scatter fraction (SF) and the noise equivalent count rate (NECR) metric were derived by the simulation of the standard sensitivity and count rate phantom in accordance with the NEMA NU 2-2001 protocol. GATE results were compared and validated against the published data in accordance with the vendor's specifications. Results: The simulated NEMA standard phantoms showed scatter fraction and sensitivity of 36%, and 4.16 cps/kBq respectively. The difference between the measured and simulated sensitivity of system was less than 1%, and scatter fraction was within the accepted range. Also maximum NECR value in 35 kBq/cc activity concentration was 92 kcps results in less than 5% difference between simulated and measured data. Conclusion: Our results demonstrated an excellent agreement between GATE simulated data and measured data. The evaluation of the PET scanner performance in the Siemens Biograph6 PET/CT scanner using Monte Carlo modeling shows that GATE is adequately accurate to describe the performance of PET system.